Method for fixing metal organic framework material Zn-BDC on surface of substrate material under assistance of polytannic acid

Through polytannic acid-assisted method, Zn-BDC is synthesized and fixed in situ on the surface of medical substrate materials, the problem of using toxic solvents and harsh conditions in the prior art is solved, and the stable fixation of substrate materials is achieved, and good antibacterial and hemostatic stasis of substrate materials is achieved. performance.

CN119386241AActive Publication Date: 2025-02-07XI AN JIAOTONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411479888.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-07
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The prior art When fixing the metal organic framework material Zn-BDC to the surface of a medical matrix, the use of toxic organic solvents and harsh reaction conditions is required, limiting its application.

Method used

Polytannic acid assisted method is used to form a polytannic acid coating on the surface of the base material by self-polymerization of tannic acid, and is synthesized and fixed in situ through multiple soaking of zinc acetate and 1,4-sodium terephthalate solution. Zn-BDC material.

Benefits of technology

The stable fixation of Zn-BDC is achieved on the surface of the substrate material, giving the substrate material good antibacterial and hemostatic properties, while avoiding the use of toxic solvents and strict reaction conditions. The method is simple and green and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005097063700000011
    Figure HDA0005097063700000011
  • Figure HDA0005097063700000012
    Figure HDA0005097063700000012
  • Figure HDA0005097063700000013
    Figure HDA0005097063700000013
Patent Text Reader

Abstract

The invention discloses a method for fixing a metal organic framework material Zn-BDC on the surface of a substrate material under the assistance of polytannic acid, which comprises the following steps: step 1, at room temperature, firstly soaking a clean substrate material in a weakly alkaline tannic acid aqueous solution, and then sequentially cleaning and drying to obtain a substrate material with the surface modified with a polytannic acid coating; 2, the substrate material with the surface modified with the polytannic acid coating is soaked in a zinc acetate solution, then cleaned and dried in sequence, then soaked in a 1, 4-sodium terephthalate solution, and then cleaned and dried in sequence; and step 3, repeating the step 2 for multiple times to obtain the substrate material modified by the metal organic framework material Zn-BDC. The method is easy to operate and environmentally friendly, Zn-BDC can be stably fixed to the surface of the substrate material, and the substrate material is endowed with good antibacterial and hemostatic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface modification of medical materials, and specifically is a method for fixing a metal organic framework material Zn-BDC on the surface of a base material with the assistance of polytannic acid. Background Art

[0002] Metal-organic framework compounds (MOFs) are a class of crystalline porous materials with a periodic network structure formed by self-assembly of inorganic metal centers (metal ions or metal clusters) and bridging organic ligands. Due to their excellent properties such as large specific surface area, high porosity, easily modified structure, good biodegradability and biocompatibility, metal-organic framework materials have been widely used in bioimaging, diagnosis, drug delivery, biosensing, photothermal therapy and other fields.

[0003] The metal organic framework material Zn-BDC is a crystalline material formed by the reaction of sodium 1,4-terephthalate and anhydrous zinc acetate. Compared with other Zn-MOFs materials with the same metal center and ligand, Zn-BDC has good stability and moisture resistance as well as stable physical and chemical properties. It is suitable for storage in different environments and is expected to be fixed on the surface of medical matrices. The zinc ions released by it participate in activating the coagulation cascade pathway and promote the adsorption, aggregation and activation of blood cells and platelets, thereby accelerating the hemostasis process. At the same time, zinc ions can give the matrix material a good antibacterial effect. Therefore, Zn-BDC needs to be durably and effectively fixed on the surface of medical matrix materials.

[0004] However, the current solvent thermal method for fixing metal organic framework materials to the substrate surface mostly involves the use of toxic organic reagents such as methanol and DMF, and the reaction conditions are harsh, which greatly limits the application of metal organic framework material Zn-BDC in the surface modification of medical materials. Therefore, it is imperative to explore a simple, efficient, energy-saving and green method for fixing Zn-BDC on the surface of medical substrate materials. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for fixing a metal organic framework material Zn-BDC on the surface of a substrate material with the assistance of polytannic acid, which is not only simple to operate and environmentally friendly, but also can stably fix Zn-BDC on the surface of the substrate material, thereby giving the substrate material good antibacterial and hemostatic properties.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for fixing a metal organic framework material Zn-BDC on a substrate surface with the aid of polytannic acid, comprising the following steps:

[0008] Step 1: first immerse a clean substrate material in a weakly alkaline tannic acid aqueous solution at room temperature, then wash and dry in sequence to obtain a substrate material with a surface modified with a polytannic acid coating;

[0009] Step 2: first immerse the substrate material with the surface modified with the polytannic acid coating in a zinc acetate solution, then wash and dry it in sequence, then immerse it in a 1,4-sodium terephthalate solution, then wash and dry it in sequence;

[0010] Step 3: Repeat step 2 multiple times to obtain a base material modified with a metal organic framework material Zn-BDC.

[0011] Furthermore, the base material in step 1 is an inner layer patch of a medical passive compression hemostatic patch, medical cotton gauze, medical cotton balls or medical sutures.

[0012] Furthermore, the concentration of the tannic acid aqueous solution in step 1 is greater than 5 mg / mL.

[0013] Furthermore, the pH value of the tannic acid aqueous solution in step 1 is 7.5-9.

[0014] Furthermore, the soaking time in step 1 is 3 to 24 hours.

[0015] Furthermore, the concentration of the zinc acetate solution in step 2 is 0.2-0.8 mol / L.

[0016] Furthermore, in step 2, the sodium 1,4-terephthalate solution is prepared by mixing a sodium hydroxide solution and a 1,4-terephthalic acid solution at a molar concentration ratio of 2.2:1, and the concentration of the sodium 1,4-terephthalate solution is 0.1 to 0.4 mol / L.

[0017] Furthermore, in step 2, the molar concentration ratio of the zinc acetate solution to the sodium 1,4-terephthalate solution is 2:1.

[0018] Furthermore, the soaking time in step 2 is 15 to 30 minutes.

[0019] Furthermore, the step 3 is to repeat the step 2 3 to 7 times.

[0020] Compared with the prior art, the present invention has the following technical effects:

[0021] The present invention first soaks the base material in a tannic acid aqueous solution, forms a polytannic acid coating on the surface of the base material through the self-polymerization of tannic acid, and uses the polytannic acid as a polyphenol to have good adhesion to base materials of different materials, so as to durably and stably fix the in-situ synthesized metal organic framework material Zn-BDC material on the surface of the base material. The zinc ions released by Zn-BDC can participate in activating the coagulation cascade pathway and promote the adsorption, aggregation and activation of blood cells and platelets, thereby accelerating hemostasis. Moreover, zinc ions have excellent inhibitory effects on both Gram-negative bacteria and Gram-positive bacteria. Furthermore, zinc element promotes the synthesis of collagen in the human body, can promote wound healing and is beneficial to skin recovery. Therefore, the base material is endowed with good antibacterial and hemostatic properties. In addition, tannic acid and polytannic acid are green and non-toxic, have excellent biocompatibility and cell affinity, and good anti-inflammatory, hemostatic and antioxidant properties. Combining them with Zn-BDC can further improve the hemostatic and anti-inflammatory properties of the base material. It can be seen that the present invention not only has a simple, efficient and green preparation method, but also provides a bionic platform for the design of functional materials, broadening the application of Zn-BDC in the surface modification of medical materials.

[0022] The invention synthesizes Zn-BDC in situ by means of the auxiliary effect of biomimetic polytannic acid, and the empty orbit of the metal zinc ion is chelated with the carboxyl group in the organic ligand 1,4-sodium terephthalate and participates in the formation of the Zn-BDC metal framework, thereby realizing the in-situ synthesis and fixation of Zn-BDC crystals on the surface of the substrate material. At the same time, the polyphenolic hydroxyl groups provided by the polytannic acid coating form coordination bonds with the inorganic metal central zinc ions, so that the Zn-BDC material is permanently and stably fixed on the surface of the substrate material, and then the Zn-BDC is permanently and stably fixed on the surface of the substrate material by means of the layer-by-layer self-assembly technology. The thickness of the Zn-BDC coating on the surface of the substrate material can be controlled by adjusting the number of repetitions of step 2 according to actual needs.

[0023] The present invention is suitable for fixing Zn-BDC on the surface of various existing substrate materials, that is, suitable for surface functional modification of various substrate materials. Not only are the raw materials easily available and low-cost, they are easy to convert into products and are conducive to industrial-scale production; moreover, no toxic or harmful substances are used or discharged during the preparation process, and it belongs to green and pollution-free processing. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 : Schematic diagram of the process of the present invention;

[0025] Figure 2 : Antibacterial effect of cotton gauze before and after Zn-BDC modification;

[0026] Figure 3 : Statistical diagram of the antibacterial rate of cotton gauze against Escherichia coli before and after Zn-BDC modification;

[0027] Figure 4 : Statistical graph of the antibacterial rate of cotton gauze against Staphylococcus aureus before and after Zn-BDC modification;

[0028] Figure 5 : BCI of cotton gauze before and after Zn-BDC modification;

[0029] Figure 6 : Statistical graph of the area of ​​wounds bandaged with cotton gauze at different time points before and after Zn-BDC modification. DETAILED DESCRIPTION

[0030] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.

[0031] According to the molar concentration ratio of 2.2:1, sodium hydroxide solution and 1,4-terephthalic acid solution were mixed to obtain a 1,4-sodium terephthalate solution with a concentration of 0.1-0.4 mol / L, which was used in Examples 1 to 9 to functionally modify the inner patch of the medical passive compression hemostatic patch, medical cotton gauze, medical cotton balls or medical sutures. Taking medical cotton gauze as an example, the process of its functional modification is shown in Figure 1 .

[0032] Example 1

[0033] Step 1, cut the medical cotton gauze into pieces, wash them with deionized water for 1 hour, put them into an oven to dry, and obtain clean medical cotton gauze;

[0034] Step 2, soaking clean medical cotton gauze in a tannic acid aqueous solution with a pH value of 8.5 and a concentration of 40 mg / mL for 12 hours, then rinsing with pure water, and then drying to obtain medical cotton gauze with a polytannic acid coating on the surface, recorded as tannic acid modified gauze;

[0035] Step 3, soaking the medical cotton gauze with a polytannic acid coating on its surface in a 0.2 mol / L zinc acetate solution for 30 min, washing it with pure water, and then drying it in an oven; then placing it in a 0.1 mol / L 1,4-sodium terephthalate solution, soaking it for 30 min, washing it with pure water, and then drying it in an oven;

[0036] Step 4: Repeat step 3 5 times to obtain medical cotton gauze modified with metal organic framework material Zn-BDC, recorded as five-layer zinc-based MOF modified gauze.

[0037] Example 2

[0038] The only difference from Example 1 is that step 2 is repeated three times, and the obtained medical cotton gauze modified with the metal organic framework material Zn-BDC is recorded as three-layer zinc-based MOF modified gauze.

[0039] Example 3

[0040] The only difference from Example 1 is that step 2 is repeated 7 times, and the obtained medical cotton gauze modified with the metal organic framework material Zn-BDC is recorded as seven-layer zinc-based MOF modified gauze.

[0041] 1) In vitro antibacterial experiment: The antibacterial properties of the prepared medical cotton gauze were evaluated by the plate coating counting method. The specific process was as follows: the original medical cotton gauze before modification, the medical cotton gauze with a surface modified with polytannic acid coating obtained in step 2 of Example 1, and the medical cotton gauze modified with metal organic framework material Zn-BDC obtained in Examples 1 to 3 were weighed and arranged in a test tube, and 10 mL of a 1.1×10 7 CFU / mL of Staphylococcus aureus suspension and 10mL of 5.2×10 7 coli bacterial suspension with 1×10 CFU / mL was incubated at 37°C for 12 h in a cell culture incubator, and then the bacterial suspension was diluted four times with normal saline at a ratio of 1:10 to 1×10 -4 Then take 1 mL of the dilution and spread it on a solid agar plate of TSA medium. Incubate at 37°C for 48 hours. The results of observation under the microscope are as follows: Figure 2 As shown, it can be seen that the medical cotton gauze modified with the metal organic framework material Zn-BDC obtained in Examples 1 to 3 has a good inhibitory effect on both the representative Gram-negative bacteria Escherichia coli and the representative Gram-positive bacteria Staphylococcus aureus;

[0042] By then recording the number of colony forming units on the solid agar plate, the antibacterial rates (i.e., the killing efficiency of bacteria) of the medical cotton gauze with a surface modified with polytannic acid coating obtained in step 2 of Example 1 and the medical cotton gauze modified with metal organic framework material Zn-BDC obtained in Examples 1 to 3 against Escherichia coli and Staphylococcus aureus were calculated. The results are shown in Figure 3 and Figure 4 , the calculation formula of the antibacterial rate is expressed as:

[0043] Antibacterial rate (%) = Nt / Nc × 100%

[0044] In the formula, Nt represents the number of colonies on the solid agar plate corresponding to the medical cotton gauze with a polytannic acid coating on the surface obtained in step 2 of Example 1 and the medical cotton gauze modified with the metal organic framework material Zn-BDC obtained in Examples 1 to 3, and Nc represents the number of colonies on the solid agar plate corresponding to the original medical cotton gauze before modification.

[0045] from Figure 3 and Figure 4 It can be seen that the medical cotton gauze with a polytannic acid coating on its surface and the medical cotton gauze modified with the metal organic framework material Zn-BDC obtained in Examples 1 to 3 have the highest antibacterial rate against Escherichia coli and Staphylococcus aureus, which is significantly better than the antibacterial rate of the original medical cotton gauze before modification.

[0046] 2) In vitro hemostasis experiment: The original medical cotton gauze before modification, the medical cotton gauze with a polytannic acid coating obtained in step 2 of Example 1, and the medical cotton gauze modified with the metal organic framework material Zn-BDC obtained in Examples 1 to 3 were cut into square samples of 10 mm × 10 mm, respectively, and placed in 50 mL centrifuge tubes, preheated at 37°C for 20 min, and then 200 μL of fresh rabbit blood anticoagulated with citrate (V / V=1:9) was dropped on the surface of the gauze in the centrifuge tube, and then incubated at 37°C for 10 min. in, then slowly add 15mL of deionized water to the centrifuge tube, shake at a speed of 30rpm for 10min, then collect the liquid in the centrifuge tube, and centrifuge at 1000rpm for 3min, and finally measure the absorbance values ​​of the corresponding liquids at 540nm of the original medical cotton gauze and the medical cotton gauze modified by Examples 1 to 3, respectively, and calculate the coagulation index BCI of the tannic acid modified gauze and the medical cotton gauze modified by the metal organic framework material Zn-BDC obtained in Examples 1 to 3 by the following formula, which is expressed as:

[0047] BCI=As / Ab×100%

[0048] In the formula, Ab represents the absorbance value of the original medical cotton gauze corresponding to the liquid, and As represents the absorbance value of the tannic acid modified gauze and the medical cotton gauze modified in Examples 1 to 3 corresponding to the liquid;

[0049] The results of in vitro hemostasis experiments were Figure 5 As shown, it can be seen that the coagulation index BCI of tannic acid modified gauze, three-layer zinc-based MOF modified gauze, five-layer zinc-based MOF modified gauze and seven-layer zinc-based MOF modified gauze are all lower than the coagulation index BCI of the original medical cotton gauze, and the coagulation index BCI of the seven-layer zinc-based MOF modified gauze is the lowest, indicating that the medical cotton gauze modified with Zn-BDC has excellent hemostatic properties, and the thicker the coating, the better the hemostatic performance.

[0050] 3) In vitro wound healing experiment: C57 male mice were selected to establish a full-thickness skin defect model. The specific modeling process was as follows: after the mice were anesthetized, the hair on the back of the mice was shaved, the skin was disinfected with iodine, and an 8-mm circular wound was made on the back of the mice with ophthalmic scissors. The original medical cotton gauze before modification, the medical cotton gauze with a polytannic acid coating obtained in step 2 of Example 1, and the modified medical cotton gauze in Example 1 were respectively covered on the wound on the back of the mice and fixed with medical tape. The wound healing conditions on the third day, the seventh day, and the fourteenth day were recorded in turn, and the changes in the wound area were calculated to evaluate the wound healing conditions. The results are shown in FIG. Figure 6 As shown, it can be seen that at different time points, the wound area covered with the medical cotton gauze modified in Example 1 is the smallest, indicating that the medical cotton gauze modified with Zn-BDC has excellent ability to promote wound healing.

[0051] Example 4

[0052] Step 1, washing the medical cotton balls with deionized water for 3 hours, and drying them in an oven to obtain clean medical cotton balls;

[0053] Step 2, soaking the clean medical cotton balls in a tannic acid aqueous solution with a pH value of 8 and a concentration of 40 mg / mL for 6 hours, then rinsing with pure water, and then drying to obtain medical cotton balls with a surface modified with a polytannic acid coating;

[0054] Step 3, soak the medical cotton ball with the polytannic acid coating on the surface in a 0.2 mol / L zinc acetate solution for 15 minutes, then wash it with pure water, and then put it in an oven to dry; then put it in a 0.1 mol / L 1,4-sodium terephthalate solution, soak it for 15 minutes, then wash it with pure water, and then put it in an oven to dry;

[0055] Step 4: Repeat step 3 three times to obtain a medical cotton ball modified with a metal organic framework material Zn-BDC.

[0056] Example 5

[0057] Step 1, washing the medical suture thread with deionized water for 1 hour, and drying it in an oven to obtain a clean medical suture thread;

[0058] Step 2, soaking a clean medical cotton ball in a tannic acid aqueous solution with a pH value of 8.5 and a concentration of 40 mg / mL for 6 hours, then rinsing with pure water, and then drying to obtain a medical suture thread with a surface modified with a polytannic acid coating;

[0059] Step 3, soaking the medical suture with a polytannic acid coating on the surface in a 0.2 mol / L zinc acetate solution for 30 min, washing it with pure water, and then drying it in an oven; then placing it in a 0.1 mol / L 1,4-sodium terephthalate solution, soaking it for 30 min, washing it with pure water, and then drying it in an oven;

[0060] Step 4: Repeat step 3 7 times to obtain a medical suture thread modified with a metal organic framework material Zn-BDC.

[0061] Example 6

[0062] Step 2, soaking the inner layer patch of the medical passive hemostatic patch in a tannic acid aqueous solution with a pH value of 8 and a concentration of 40 mg / mL for 4 hours, then rinsing with pure water, and then drying to obtain the inner layer patch of the medical passive hemostatic patch with a polytannic acid coating modified on the surface;

[0063] Step 3, soak the inner layer of the medical passive hemostatic patch with a polytannic acid coating on its surface in a 0.2 mol / L zinc acetate solution for 30 min, wash it with pure water, and then put it in an oven for drying; then put it in a 0.1 mol / L 1,4-sodium terephthalate solution, soak it for 30 min, wash it with pure water, and then put it in an oven for drying;

[0064] Step 4: Repeat step 3 5 times to obtain the inner layer patch of the medical passive compression hemostatic patch modified with the metal organic framework material Zn-BDC.

[0065] Example 7

[0066] Step 1, cut the medical cotton gauze into pieces, wash them with deionized water for 1 hour, put them into an oven to dry, and obtain clean medical cotton gauze;

[0067] Step 2, soaking clean medical cotton gauze in a tannic acid aqueous solution with a pH value of 7.5 and a concentration of 40 mg / mL for 18 hours, then rinsing with pure water, and then drying to obtain medical cotton gauze with a polytannic acid coating on the surface, recorded as tannic acid modified gauze;

[0068] Step 3, soaking the medical cotton gauze with a polytannic acid coating on its surface in a 0.5 mol / L zinc acetate solution for 15 minutes, washing it with pure water, and then drying it in an oven; then placing it in a 0.25 mol / L 1,4-sodium terephthalate solution, soaking it for 15 minutes, washing it with pure water, and then drying it in an oven;

[0069] Step 4: Repeat step 3 7 times to obtain medical cotton gauze modified with metal organic framework material Zn-BDC, recorded as five-layer zinc-based MOF modified gauze.

[0070] Example 8

[0071] Step 1, washing the medical cotton balls with deionized water for 3 hours, and drying them in an oven to obtain clean medical cotton balls;

[0072] Step 2, soaking the clean medical cotton balls in a tannic acid aqueous solution with a pH value of 9 and a concentration of 40 mg / mL for 24 hours, then rinsing with pure water, and then drying to obtain medical cotton balls with a surface modified with a polytannic acid coating;

[0073] Step 3, soak the medical cotton ball with the polytannic acid coating on the surface in a 0.8 mol / L zinc acetate solution for 20 minutes, then wash it with pure water, and then put it in an oven to dry; then put it in a 0.4 mol / L 1,4-sodium terephthalate solution, soak it for 20 minutes, then wash it with pure water, and then put it in an oven to dry;

[0074] Step 4: Repeat step 3 5 times to obtain a medical cotton ball modified with a metal organic framework material Zn-BDC.

Claims

1. A method for fixing a metal organic framework material Zn-BDC on the surface of a substrate material with the aid of polytannic acid, characterized in that: The steps include: Step 1: first immerse a clean substrate material in a weakly alkaline tannic acid aqueous solution at room temperature, then wash and dry in sequence to obtain a substrate material with a surface modified with a polytannic acid coating; Step 2: first immerse the substrate material with the surface modified with the polytannic acid coating in a zinc acetate solution, then wash and dry it in sequence, then immerse it in a 1,4-sodium terephthalate solution, then wash and dry it in sequence; Step 3: Repeat step 2 multiple times to obtain a base material modified with a metal organic framework material Zn-BDC.

2. The method for fixing the metal organic framework material Zn-BDC on the surface of a substrate material with the aid of polytannic acid according to claim 1, characterized in that: In the step 1, the base material is the inner layer patch of a medical passive compression hemostatic patch, medical cotton gauze, medical cotton balls or medical sutures.

3. The method for fixing the metal organic framework material Zn-BDC on the surface of a substrate material with the aid of polytannic acid according to claim 1, characterized in that: The concentration of the tannic acid aqueous solution in step 1 is greater than 5 mg / mL.

4. The method for fixing the metal organic framework material Zn-BDC on the surface of a substrate material with the aid of polytannic acid according to claim 1, characterized in that: The pH value of the tannic acid aqueous solution in step 1 is 7.5-9.

5. The method for fixing the metal organic framework material Zn-BDC on the surface of a substrate material with the aid of polytannic acid according to claim 1, characterized in that: The soaking time in step 1 is 3 to 24 hours.

6. The method for fixing the metal organic framework material Zn-BDC on the surface of a substrate material with the aid of polytannic acid according to claim 1, characterized in that: The concentration of the zinc acetate solution in step 2 is 0.2-0.8 mol / L.

7. The method for fixing the metal organic framework material Zn-BDC on the surface of a substrate material with the aid of polytannic acid according to claim 6, characterized in that: In step 2, the 1,4-sodium terephthalate solution is prepared by mixing a sodium hydroxide solution and a 1,4-terephthalic acid solution at a molar concentration ratio of 2.2:1, and the concentration of the 1,4-sodium terephthalate solution is 0.1-0.4 mol / L.

8. The method for fixing the metal organic framework material Zn-BDC on the surface of a substrate material with the aid of polytannic acid according to claim 7, characterized in that: The molar concentration ratio of the zinc acetate solution to the sodium 1,4-terephthalate solution in step 2 is 2:

1.

9. The method of fixing the metal organic framework material Zn-BDC on the surface of a substrate material with the aid of polytannic acid according to claim 1, characterized in that: The soaking time in step 2 is 15 to 30 minutes.

10. The method for fixing the metal organic framework material Zn-BDC on the surface of a substrate material with the aid of polytannic acid according to claim 1, characterized in that: The step 3 is to repeat the step 2 3 to 7 times.

Citation Information

Patent Citations

  • Multifunctional material integrating bactericidal and hemostatic properties and chemical and biological warfare agent protective properties and preparation method of multifunctional material

    CN106267300A

  • Application of polyphenol metal ion coagulation-promoting coating in preparation of hemostatic material

    CN113069588A

  • Preparation method and application of antibacterial bacterial cellulose based wound dressing

    CN116510058A

  • Letter model design algorithm

    KR1020210048166A